Pemetaan Sebaran Rafflesia SP Berbasis WebGIS pada Kawasan Taman Nasional Kerinci Seblat (TNKS) di Nagari Sungai Gambir Sako Tapan Kecamatan Ranah Ampek Hulu Tapan - Sanny, Fica Fadhilia; Yulfa, Arie (YASIN, 2024)
Rafflesia is a unique type of plant and is the largest single flower in the world. One form of management of the TNKS area is to make observations related to the Rafflesia distribution point. Identifying the function needed in the information system related to the Rafflesia SP Family in the TNKS area in Nagari Sungai Gambir Sako Tapan. This type of research is quantitative. Data processed with prototype models is a technique for collecting certain information about the needs of the system. This method will analyze the data using the likert scale. In the evaluation stage, the system uses Usability Testing using the SUS (System Usability Scale) questionnaire method to look for system weaknesses and flaws. This study resulted in 1. Features of the WebGIS design include the addition, modification, and deletion of Rafflesia SP coordinate points. 2. Based on the results of the product test as a user, a response was obtained with an average score of 78 which means that the user agrees with the functions (menus and features) on WebGIS that are running well, and can be executed.